Global Pandemic: Impacts and Solutions - Akinyosoye Kehinde; Melis Kaytaz (Lembaga Riset Ilmiah, 2022)
This study aims to introduce a framework that captures the impact and potential responses to the ongoing COVID-19 pandemic. To do that, we conducted telephone interviews with ten entrepreneurs who operate companies in Africa. The COVID-19 pandemic has been going on for almost 2 years and is expected to continue until the end of 2022. This will certainly cause some companies to experience business failure if entrepreneurs do not respond appropriately. Adequate. The data collected for analysis were transcribed, arranged chronologically, coded, and analyzed thematically using NVivo. Our findings reveal that, during the pandemic, businesses experience limited opening hours, decreased patronage of their clients, lower turnover, and demotivation of employees. In response, business owners should consider reorganizing their business activities, maintaining client relationships, and taking advantage of available support measures. Our findings have profound theoretical and practical implications. Entrepreneurs and policymakers, offer insight into the shape of the challenges businesses face during the pandemic. It also provides response activities that entrepreneurs can adopt to reduce the impact of the epidemic on their company’s performance. For the field of entrepreneurship, this raises the need to integrate public health (health-related issues) into the study of entrepreneurship and consider the varying degrees of influence on business performance